2015
DOI: 10.1002/cncr.29260
|View full text |Cite
|
Sign up to set email alerts
|

Downstage migration after neoadjuvant chemoradiotherapy for rectal cancer: The reverse of the Will Rogers phenomenon?

Abstract: Downstaging after neoadjuvant treatment is increasingly used as a prognostic factor and surrogate endpoint in clinical trials. However, in recent trials of neoadjuvant 5‐fluorouracil–based chemoradiotherapy for rectal cancer, downstaging did not translate into a benefit with regard to either disease‐free survival (DFS) or overall survival. By analyzing the 10‐year outcome data of the German CAO/ARO/AIO‐94 phase 3 trial, the authors demonstrated that significantly fewer patients had poor prognostic features (eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 11 publications
3
11
0
1
Order By: Relevance
“…However, this study did not include down-staging in the multivariate analysis. T down-staging has been shown to be a more significant prognostic factor than regression in many reports so both factors should be analysed separately (9,10). In our series we have confirmed that both factors show prognostic influence in the univariate survival analysis but in the multivariate analysis down-staging showed independent prognostic value for DFS and regression for OS.…”
Section: Discussionsupporting
confidence: 78%
“…However, this study did not include down-staging in the multivariate analysis. T down-staging has been shown to be a more significant prognostic factor than regression in many reports so both factors should be analysed separately (9,10). In our series we have confirmed that both factors show prognostic influence in the univariate survival analysis but in the multivariate analysis down-staging showed independent prognostic value for DFS and regression for OS.…”
Section: Discussionsupporting
confidence: 78%
“…Because any improvement in overall survival may require better control of DM, those studies evaluating 5‐FU based preoperative CRT failed to find improved overall and/or disease‐free survival. In this perspective, Fokas et al recently reported similar results to our study that ypStage II was found to be at a higher risk of developing DM and poorer disease‐free survival than pStage II. A trend toward a worse outcome in ypStage III versus pStage III did not reach statistical significance in the ad hoc analysis of the CAO/AIO/ARO‐94 phase 3 trial of German Rectal Cancer Study Group ; this was surprisingly similar to our analysis in stage III rectal cancer, although they compared disease‐free survival rather than DM.…”
Section: Discussionsupporting
confidence: 90%
“…In this perspective, Fokas et al recently reported similar results to our study that ypStage II was found to be at a higher risk of developing DM and poorer disease‐free survival than pStage II. A trend toward a worse outcome in ypStage III versus pStage III did not reach statistical significance in the ad hoc analysis of the CAO/AIO/ARO‐94 phase 3 trial of German Rectal Cancer Study Group ; this was surprisingly similar to our analysis in stage III rectal cancer, although they compared disease‐free survival rather than DM. The authors suggested that “downstaging migration” after preoperative CRT resembles the reverse of the Will Rogers phenomenon and is not a reliable endpoint for long‐term outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Fokas et al . have suggested that ypTNM downstaging might not be a reliable indicator of therapeutic efficacy and prognosis.…”
Section: Introductionmentioning
confidence: 99%